Rural underemployment and urbanisation: Insights from a 9-year panel from Malawi - Van Cappellen, Hanne; De Weerdt, Joachim (Oxford University Press, 2025)
Rural labour markets in Africa are frequently characterised by underemployment, with farmers unable to fully deploy throughout the year one of their most important assets—their labour. Using a nine-year panel data set on 1,407 working-age adults from rural Malawi, we document changes in rural underemployment over this period and how they are associated with urbanisation. Nearby urban growth is linked to increased hours worked in casual labour (ganyu) and in non-agricultural sectors, at the expense of work on the household farm. Improved urban access is also associated with a small increase in wage labour and, at the intensive margin, with hours supplied in household enterprises. We draw lessons from these results for policies, investments and interventions to leverage urban growth for rural development.